Bilateral and Multilateral Coauthorship and Citation Impact: Patterns in UK and US International Collaboration - Adams, Jonathan; Gurney, Karen A. (Frontiers in Research Metrics and Analytics, 2018)
International collaboration makes up an increasing, high citation-impact share of research output, but the UK’s collaboration with key partners is threatened by its decision to leave the EU. Data show that about 85% of US and UK international collaboration is with only one or two partners, usually among other “leading” research economies. Although highly multinational research (10 or more authors) is growing more rapidly than total research output, it actually remains scarce (about 1% of all collaboration) among the established research economies. Analysis also shows that the “citation bonus” contributed by international collaboration is in fact both specific and limited; it should, therefore, be interpreted with some care. For example, citation impact trends look different for two-country and multi-country collaborations involving the same countries. Impact also increases but then plateaus with increasing numbers of partners. Further, we find that massively multinational papers are of such a different kind that we suggest they should be excluded from standard citation analysis.